Characterization of Plant-Growth-Promoting Rhizobacteria for Tea Plant (Camellia sinensis) Development and Soil Nutrient Enrichment - Mengjiao Wang; Haiyan Sun; Huiping Dai; Zhimin Xu (Plants)
Plant-growth-promoting rhizobacteria (PGPR) play an important role in plant growth and rhizosphere soil. In order to evaluate the effects of PGPR strains on tea plant growth and the rhizosphere soil microenvironment, 38 PGPR strains belonging to the phyla Proteobacteria with different growth-promoting properties were isolated from the rhizosphere soil of tea plants. Among them, two PGPR strains with the best growth-promoting properties were then selected for the root irrigation. The PGPR treatment groups had a higher Chlorophyll (Chl) concentration in the eighth leaf of tea plants and significantly promoted the plant height and major soil elements. There were significant differences in microbial diversity and metabolite profiles in the rhizosphere between different experimental groups. PGPR improved the diversity of beneficial rhizosphere microorganisms and enhanced the root metabolites through the interaction between PGPR and tea plants. The results of this research are helpful for understanding the relationship between PGPR strains, tea plant growing, and rhizosphere soil microenvironment improvement. Moreover, they could be used as guidance to develop environmentally friendly biofertilizers with the selected PGPR instead of chemical fertilizers for tea plants.